Wake me up before you GO-GARCH - H. Peter Boswijk; Roy van der Weide (Tinbergen Institute, 2006)
In this paper we present a new three-step approach to the estimation of Generalized Orthogonal GARCH (GO-GARCH) models, as proposed by van der Weide (2002). The approach only requires (non-linear) least-squares methods in combination with univariate GARCH estimation, and as such is computationally attractive, especially in larger-dimensional systems, where a full likelihood optimization is often infeasible. The effectiveness of the method is investigated using Monte Carlo simulations as well as a number of empirical applications.
Keywords: C13; C32; 330; Multivariate GARCH; Non-Linear Least-Squares; Maximum Likelihood